Teacher-student discourse in active learning lectures: case studies from undergraduate physics. Issue 7 (3rd October 2018) - Wood, Anna K.; Galloway, Ross K.; Sinclair, Christine; Hardy, Judy
ABSTRACT: In this paper we develop knowledge of the discourse that takes place between teacher and students in two large undergraduate classes which use a flipped, active learning approach. In flipped classes students encounter the content through pre-class resources, freeing up class time for more active engagement with the material. This results in increased opportunities for teacher-student interactions which may be beneficial for learning. Our aim here is to explore the nature and purposes of these dialogues. Two case studies from introductory physics classes at the University of Edinburgh are analysed through a sociocultural perspective. Three main purposes of dialogues are observed: (1) Involving students in sense-making, (2) Guided expert modelling and (3) Wonderment questions. We found that the dialogues predominantly use a triadic Initiation, Response, Feedback (IRF) format and are authoritative in nature, but work together to create an interactive learning environment that can be described as 'ideologically dialogic'